Blocking Public Participation : The Use of Strategic Litigation to Silence Political Expression - Sheldrick, Byron M (Book collections on Project MUSE., 2014)
"Blocking Public Participation examines the different types of litigation and causes of action that frequently form the basis of SLAPPs, (strategic litigation against public participation) and how these lawsuits transform political disputes into legal cases, thereby blocking political engagement. The resource imbalance between plaintiffs and defendants allows the plaintiffs to tie up defendants in complex and costly legal processes. The book also examines the dangers SLAPPs pose to political expression and to the quality and integrity of our democratic political institutions. Finally, the book examines the need to regulate SLAPPs in Canada and assesses various regulatory proposals."--Jacket